Developing an interactive web-based learning program on skin cancer: the learning experiences of clinical educators. - Shaikh WR; Geller A; Alexander G; Asgari MM; Chanange GJ; Dusza S; Eide MJ; Fletcher SW; Goulart JM; Halpern AC; Landow S; Marghoob AA; et al. (Journal of Cancer Education, 2012)
Web-based learning in medical education is rapidly growing. However, there are few firsthand accounts on the rationale for and development of web-based learning programs. We present the experience of clinical educators who developed an interactive online skin cancer detection and management course in a time-efficient and cost-efficient manner without any prior skills in computer programming or technical construction of web-based learning programs. We review the current state of web-based learning including its general advantages and disadvantages as well as its specific utility in dermatology. We then detail our experience in developing an interactive online skin cancer curriculum for primary care clinicians. Finally, we describe the main challenges faced and lessons learned during the process. This report may serve medical educators who possess minimal computer programming and web design skills but want to employ the many strengths of web-based learning without the huge costs associated with hiring a professional development team.